LEGAL REGULATION OF FINANCIAL INTELLIGENCE OF ENTERPRISES IN THE CONDITIONS OF INCREASING INFLUENCE OF MODERN FACTORS - Blikhar, Mariia (Socio-economic relations in the digital society, 2024)
The purpose of the article is to study the peculiarities and problematic aspects of the legal regulation of financial intelligence of enterprises in the conditions of increasing influence of modern factors. Based on the results of the conducted research, it was established that at the current stage of the functioning of the national legal system, the organizational and legal mechanisms for regulating financial intelligence at the enterprise level are weak and require revision, improvement and strengthening. It was established that when considering financial intelligence at the enterprise level, the main emphasis is placed on its structural component, such as competitive intelligence. The ambiguity and specificity of the legal basis for the regulation of financial intelligence of enterprises have been revealed, the main difference of which is the formation of legal norms in interdependence with the peculiarities of the country's legal system and its affiliation to the Anglo-Saxon or Romano-Germanic legal system. It has been proven that the financial intelligence system functions successfully at such well-known global companies as Procter & Gamble and Motorola. The main problems of the introduction and implementation of intelligence activities at enterprises were identified, most of which are due to the insufficient number and inefficiency of the management of information, labour and technological resources of the economic entity. The main vectors of improving the legal regulation of financial intelligence of enterprises in the conditions of increasing influence of modern factors are proposed, in particular: (1) the urgency and necessity of implementing the legislative regulation of the economic and legal category "financial intelligence of an enterprise" is substantiated; (2) the necessity of enshrining at the legislative level the basic organizational and legal principles of increasing responsibility for committing acts related to the unauthorized receipt, use and transfer of information at the enterprise has been proven.
Keywords: financial intelligence; regulatory and legal support; legislative acts; intelligence activity; competitive intelligence; enterprise